Analisis Potensi Bahaya Lingkungan Kerja pada Usaha Penjahit Y Di Kota Palembang - Hanani, Atidira Dwi (Syntax Idea, 2021)
There are many complaints and health problems felt by tailors which in turn can lead to high rates of occupational diseases. Occupational diseases can occur due to potential hazards in the work environment. It is important to analyze the potential hazards of the work environment as one of the basic considerations for avoiding occupational accidents and diseases. This study aims to analyze the potential hazards of the work environment in Y Tailor which can be used as a basis for improvement as an effort to create a safe work environment. This study used a qualitative method by conducting in-depth interviews and observations to assess the potential hazards in Y Tailor. The results showed various potential hazards in the work environment at Y Tailor, such as physical, chemical, biological, ergonomic, and psychological hazards. This has caused complaints and health problems felt by the workers at Y Tailor, such as headaches, respiratory problems, musculoskeletal disorders, and work stress. There needs improvements in management related to a safe work environment as an effort to maintain the safety and health of workers at Y Tailor.